2017
DOI: 10.1111/cfs.12381
|View full text |Cite
|
Sign up to set email alerts
|

Participation of youth in decision‐making procedures during residential care: A narrative review

Abstract: Participation in decision-making procedures of young people in care is considered a key element that affects their current or future living circumstances and might improve the quality of decisionmaking on and delivery of provided services.This narrative literature review, covering the period 2000-2016, focuses on the opportunities of young people to participate, the challenges and facilitators to participation, and the outcomes of care related to participation.Sixteen studies met our search criteria. Several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 46 publications
(155 reference statements)
2
35
1
3
Order By: Relevance
“…Although there are very good examples of cooperation and partnership in matching decision‐making, there is a belief among practitioners that they know what is in the best interests of children, birth parents and foster carers. However, even if unintentionally, this practice may harm the relationship between them and the stakeholders (Bessell, ; Sellick, ; Ten Brummelaar et al, ), and negatively affect the foster care placement (Bell, ; Knorth et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are very good examples of cooperation and partnership in matching decision‐making, there is a belief among practitioners that they know what is in the best interests of children, birth parents and foster carers. However, even if unintentionally, this practice may harm the relationship between them and the stakeholders (Bessell, ; Sellick, ; Ten Brummelaar et al, ), and negatively affect the foster care placement (Bell, ; Knorth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Participation in decision‐making empowers stakeholders and can diminish negative effects (Bell, ; Knorth et al, ). Children who participate in decisions feel more valued and are less likely to experience desperation, anxiety or anger towards a care decision (Bessell, ; Ten Brummelaar et al, ). Although children have a right to have their views heard in decisions related to their lives (United Nations Convention on the Rights of the Child), they are often inadequately involved in decision‐making processes (Arbeiter and Toros, ; Bessell, ; Krappmann, ; Ten Brummelaar et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In child welfare and child protection services, children's participation is often perceived as a challenging goal to achieve (ten Brummelaar, Harder, Kalverboer, Post, & Knorth, 2017;Vis, Strandbu, Holtan, & Thomas, 2011). On the one hand research has shown that social workers across Western countries acknowledge the importance of hearing children, building trust to ensure effective communication (Archard & Skivenes, 2009) as well as involvingchildren in decision-making processes (Berrick, Dickens, Pösö, & Skivenes, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Children separated from their families and living in public care very often find themselves in situations where their opinions should be taken into consideration. The child's involvement in decision-making can take place in a variety of contexts, including the choice of daily activities, social and psychological support arrangements, decisions with regard to the child's future, e. g. where and with whom he or she would live (Ten Brummelaar et al 2018). Child participation increasingly attracts the attention of researchers outside Russia.…”
mentioning
confidence: 99%